Recent advances in polymer network liquid crystal spatial light modulators - Sun, Jie; Wu, Shin-Tson (Journal of polymer science. Part B, Polymer physics, 2014)
ABSTRACT Polymer network liquid crystal (PNLC) spatial light modulators are attractive for display and photonic applications because they can achieve submillisecond response time while keeping a large phase change. However, their on‐state scattering caused by the grain boundary of LC multidomains hinders their applications. In this article, we review recent progress on the development of scattering‐free PNLCs extending from short‐wavelength infrared to visible region by reducing the domain sizes to ∼200 nm through low temperature curing process. To reduce operation voltage, both transmissive and reflective modes, LC material properties (birefringence and dielectric anisotropy), polymer composition and concentration, and pretilt angle effect are analyzed. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2014, 52, 183–192 Polymer network liquid crystal (PNLC) spatial light modulators are attractive for display and photonic applications because they can achieve a fast response time while keeping a large phase modulation depth. However, their power on scattering caused by the grain boundary of LC multidomains hinders their application. In this article, scattering free PNLC spatial light modulators with submillisecond response time are reported from λ = 1.55 μm and λ = 1.06 μm to visible wavelengths.